Exchange rate and regional divergences: The Swiss case - Corpataux, José; Crevoisier, Olivier; Thierstein, Alain (My University, 2002)
CORPATAUX J., CREVOISIER O. and THIERSTEIN A. (2002) Exchange rate and regional divergences: the Swiss case, Reg. Studies 36, 611-626. From 1975 to 1995, the Swiss franc appreciated in a near constant manner compared with the currencies of all of the country's commercial partners. This paper will seek to demonstrate that the various regions in Switzerland evolve differently when faced with a continuously appreciating currency. The paper is not in the nature of an econometric study and will not seek to quantify the gains and losses of each region, but it will view their structural evolution via the effect of the exchange rates. Faced with the appreciation of the Swiss franc and based on their productive specialities, some regions suffer badly from this, whilst others cope with it and even thrive on it. It is thus possible to openly question the consequences of the Swiss National Bank's monetary policy: has domestic industry been sacrificed in favour of financial activities? Is the continuous rise of the Swiss franc increasing regional disparities in Switzerland? The paper first discusses the theories that establish a link between the exchange rate and the evolution of regional production systems. All these theories draw conclusions that can vary radically. Furthermore, they are usually based on the assumption of homogenous national territories. The second part contains a description of the methodology applied, which is based on the concept of regional production systems (RPSs). The impact of the exchange rate on RPSs is explained by means of three criteria: sectorial specialization and basic source of income within RPSs; the presence or absence of large firms; and the innovative capacity of the RPSs. The third part of the paper illustrates five examples of RPSs, each of which has evolved in a radically different way over the relevant period. Lastly, a link is established between the regional divergences and the evolution of the exchange rate in the whole of Switzerland from 1975 to 1995. The conclusion draws a parallel between the evolution in Switzerland and the tensions that could arise between the regions and the nations constituting the Euro zone.
Keywords: exchange rate; optimal monetary zone; regional production systems; industrial regions; tourist regions; financial centres; Euroland